Mediastinal tumors of thyroid origin - Suiffet, Walter (Cirugía del Uruguay, 1974)
Thoracic goiters (B.T.) are defined as all those goiters that are permanently located in the thorax (totally or partially) or transient, behave according to its mediastinal topography, like a mediastinal tumor (T.M.).